Prospective audit and feedback on antibiotic use in neonatal intensive care: a retrospective cohort study - Nisha Thampi; Prakesh S. Shah; Sandra Nelson; Amisha Agarwal; Marilyn Steinberg; Yenge Diambomba; Andrew M. Morris (BMC Pediatrics, 2019)
Abstract Background Antimicrobial stewardship programs potentially lead to appropriate antibiotic use, yet the optimal approach for neonates is uncertain. Such a program was implemented in a tertiary care neonatal intensive care unit in October 2012. We evaluated the impact of this program on antimicrobial use and its association with clinical outcomes. Methods In a retrospective cohort study, we examined 1580 neonates who received antimicrobials in the 13-months before and 13-months during program implementation. Prospective audit and feedback was given 5 days a week on each patient who was receiving antibiotic. Pharmacy and microbiology data were linked to clinical data from the local Canadian Neonatal Network database. The primary outcome was days of antibiotic therapy per 1000 patient-days; secondary outcomes included mortality, necrotizing enterocolitis, and antibiotic duration for culture-positive and culture-negative late-onset sepsis. The breadth of antibiotic exposure was compared using the Antibiotic Spectrum Index. Results Overall antibiotic use decreased to 339 days of therapy per 1000 patient-days from 395 (14%, P < 0.001), without an increase in mortality. There was no difference in duration of therapy in culture-negative or culture-positive sepsis, rates of necrotizing enterocolitis, or breadth of antibiotic exposure. Fewer antibiotic starts occurred during program implementation (63% versus 59%, P < 0.001). The use of narrow-spectrum agents decreased (P < 0.001) whereas the use of cefotaxime increased (P = 0.016) during program implementation. Conclusions Daily prospective audit and feedback was not associated with a change in antibiotic duration or clinical outcomes, however there were fewer babies started on antibiotics, suggesting that additional interventions are required to inform and sustain changes in antibiotic prescribing practices.